Effect of Dietary Starch-to-Fat Ratio on Lipid Metabolism, Inflammation, and Microbiota of Multiparous Sow and Newborn Piglets - Wenhui Wang; Zirou Yu; Xindi Yin; Zijie Wang; Song Xu; Chenyu Shi; Jianjun Zang; Hu Liu; Fenglai Wang (Agriculture, 2023)
This experiment aimed to evaluate the effects of dietary starch-to-fat ratio on reproductive performance and lipid metabolism of sows and newborn piglets. A total of 75 Landrace × Yorkshire multiparous sows at d 84 of gestation were selected and randomly divided into three groups based on body weight. From d 85 of gestation to farrowing, sows were fed one of three dietary starch-to-fat ratios (20:1, 10:1, and 5:1). Dietary high starch-to-fat ratio increased the birth weight of piglets (p < 0.05). The apparent total digestibility of dry matter, organic matter, and gross energy of sows was improved by an increasing starch-to-fat ratio during gestation (p < 0.05). Decreased dietary starch-to-fat ratio increased the concentration of plasma triglycerides, total cholesterol, and GSH-Px in sows (p < 0.05). During parturition, sows had increased plasma interleukin (IL) -1β, IL-6, and tumor necrosis factor α in the low ratio group (p < 0.05). The relative abundance of Streptococcaceae in the low ratio group was significantly higher (p < 0.05). The medium dietary starch-to-fat ratio significantly increased the concentrations of short chain fatty acids. In conclusion, this study suggested that for sows a diet with ahigh starch to fat ratio could ameliorate lipid metabolism disorder and maternal inflammation during late gestation.